Analisis Efektivitas Video “Good Health And Well-Being-Nory” Berbasis Motion Graphic Menggunakan EPIC Model - Adhe Tertiasusman; Teddy Setyawan (Politeknik Negeri Batam, 2022)
Many people think that people who are physically fitis a healthy person, whereas a healthy person is a person whophysically and mentally or physically healthy. When mental healthIf a person's spirituality is disturbed, he will experience health problemsMental health In Indonesia alone, there are around 14 million people over the age of 15years with mental health problems. One of the solutions thatoffered from the problem is through the